Solvent-free ethyl oleate synthesis mediated by lipase from Candida antarctica B adsorbed on polypropylene powder - Foresti, María Laura; Ferreira, María Luján (Catalysis Today)
The enzymatic synthesis of ethyl oleate by direct esterification of oleic acid and ethanol in solvent-free media has been studied. Native lipase from Candida antarctica B and Candida antarctica B lipase adsorbed on powdered polypropylene were used with promising results. The influence of different parameters such us temperature, mass of lipase and aqueous content of reaction medium, on conversion profiles has been carefully studied. High water contents that ensured the co-existence of two liquid phases gave the best results, with conversions of up to 78.6% in 7 h of reaction. Pre-treatment with octane/buffer mixtures significantly reduced agglomeration of the immobilized catalyst, leading to important increments in specific enzymatic activity, when compared with non-pre-treated biocatalyst. Lipase desorption from PP has also been studied. © 2005 Elsevier B.V. All rights reserved. Fil: Foresti, María Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Planta Piloto de Ingeniería Química. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química; Argentina Fil: Ferreira, María Luján. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Planta Piloto de Ingeniería Química. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química; Argentina